Positioning the Chinese Princess of Peace in World Literature - Novita Dewi (STKIP Singkawang, 2019)
The novel Putri Cina or The Chinese Princess by Sindhunata builds on the intertextuality of various texts such as myths, chronicles, history, and pop culture. In the light of René Girard’s theory of desire, revenge, and scapegoating, this study aims (1) to show the inter-relationship among the texts in question; and (2) placing this novel in the work of World Literature. Through qualitative research methods and close reading techniques, this study finds out that Putri Cina recounts the history of conflicts to promote peace rather than revenge. The novel narrates such conflicts as the war between the descendants of the Javanese kings; the feud between the Chinese and Javanese people in colonial time; and the May 1998 ethnic riots in Indonesia. It concludes that it is necessary to circulate the narrative of the Chinese Princess as a peace ambassador in World Literature through the process of adaptation and translation. In a world prone to conflict, literary works can be effective agents of transformation.